If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 1 = (-5) Reorder the terms: 1 + 2y = (-5) 1 + 2y = -5 Solving 1 + 2y = -5 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 2y = -5 + -1 Combine like terms: 1 + -1 = 0 0 + 2y = -5 + -1 2y = -5 + -1 Combine like terms: -5 + -1 = -6 2y = -6 Divide each side by '2'. y = -3 Simplifying y = -3
| -6w+8=-6w-(-8) | | x=(3y-24)/2 | | 7(v-4)-3v=-32 | | -2r+4(-3r+3)=-15-5r | | 8/3x+1/3x+32/3+5/3x | | 7x+14=2x+4 | | 8/3x+1/3x+102/3+5/3x | | 16z-24=16z-24 | | 0=r+12 | | 2m-5=(-3) | | 6y+8(y+6)=34 | | 5z=4z+1 | | 3(x-2)+3=60 | | 5(x-4)+8(2x-2)=6(x+1)+5(x+10) | | 18-16/(2*2+4) | | 8x-4-3x=x+5+x | | 4+4m=25 | | 16+k=18 | | K+6=-9-2k | | 3(m-3)-2=-3+4m | | 15x=4x-2 | | -30=-15p | | 8/3x+1/3x=102/3+5/3x | | -6+14-z/m | | 12-12x= | | 3r+10=15r-8 | | N-3x=-3 | | f(-20)=10(-20)+3 | | 15c-10+8=43 | | 8w^2+5w+2=0 | | M+(-17)=-16 | | w^2-12w+35=0 |